Governance of Financial Supervisors and its Effects – a Stocktaking Exercise - Marc Quintyn (SUERF - The European Money and Finance Forum, 2007)
The attention for the governance of financial sector supervisors is of a recent date. The debate has risen to the fore as part of the wider discussion about the appropriate institutional organization of financial supervision and the drive for compliance with international best practices in the regulatory field. This paper takes stock of the regulatory governance debate. We first discuss the main premise of the paper, that regulatory governance plays a pivotal role in instilling financial sector governance, which in turn is a key source of corporate governance in the nonfinancial sector (the governance nexus). Having established this premise, we identify the main pillars for regulatory governance-independence, accountability, transparency, and integrity. The next two sections take a look at where we stand in practice. First, we review to what extent recent reforms of supervisory structures worldwide are embracing the four pillars underlying regulatory governance. We find that policy makers are gradually making efforts to improve the foundations for regulatory governance. However, further convincing, in particular of the beneficial effects of accountability, seems necessary. Secondly, we review a number of studies that assess the impact of (aspects of) regulatory governance on the soundness of the banking system (an indicator of good financial system corporate governance), or other aspects of the governance nexus. Most studies show a positive impact of stronger regulatory governance frameworks on the soundness of the financial system. However, further empirical evidence to strengthen the case for good regulatory governance seems desirable.
Keywords: G18; G20; G28; G34; G38; L50; 330; Financial sector supervision; financial regulation; regulatory governance; corporate governance; public sector governance; Aufsichtsbehörde; Finanzmarkt; Governance-Ansatz; Welt